Health Assets in a Global Context Theory, Methods, Action - Morgan, Antony; Ziglio, Erio.; Davies, Maggie; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Health Assets in a Global Context: Theory, Methods, Action Edited by Antony Morgan, Maggie Davies, and Erio Ziglio As global health inequities continue to widen, policymakers are redoubling their efforts to address them. Yet the effectiveness and quality of these programs vary considerably, sometimes resulting in the reverse of expected outcomes. While local political issues or cultural conflicts may play a part in these situations, an important new book points to a universal factor: the prevailing deficit model of assessing health needs, which puts disadvantaged communities on the defensive while ignoring their potential strengths. The asset model proposed in Health Assets in a Global Context offers a necessary complement to the problem-focused framework by assessing multiple levels of health-promoting aspects in populations, and promoting joint solutions between communities and outside agencies. The book provides not only rationales and methodologies (e.g., measuring resilience and similar elusive qualities) but also concrete examples of asset-based initiatives in use across the world on the individual and community levels, including: • Strengthening the assets of disadvantaged women (Germany). • Sustainable community-based development programs (India). • Using parental assets to control child malaria (West Africa). • Asset/evidence-based health promotion in the schools (Romania). • Evaluating asset-based programs (Latin America). • Using social capital to promote health equity (Australia). Health Assets in a Global Context offers a new, positive lens for viewing the world’s most resistant public health crises, making it fundamental reading for researchers and graduate students in public health, especially those involved in health promotion, health disparities, social determinants of health, and global health.
Conceptualising the Notion of Health Assets -- Revitalising the Public Health Evidence Base: An Asset Model -- A Salutogenic Approach to Tackling Health Inequalities -- A Theoretical Model of Assets: The Link Between Biology and the Social Structure -- Asset Mapping in Communities -- Assets Based Interventions: Evaluating and Synthesizing Evidence of the Effectiveness of the Assets Based Approach to Health Promotion -- Building an Evidence Base on Assets and Health -- Resilience as an Asset for Healthy Development -- How to Assess Resilience: Reflections on a Measurement Model -- Measuring Children’s Well-Being: Some Problems and Possibilities -- The Relationship Between Health Assets, Social Capital and Cohesive Communities -- Health Assets in Action -- Community Empowerment and Health Improvement: The English Experience -- Strengthening the Assets of Women Living in Disadvantaged Situations: The German Experience -- Sustainable Community-Based Health and Development Programs in Rural India -- The Application and Evaluation of an Assets-Based Model in Latin America and the Caribbean: The Experience with the Healthy Settings Approach -- Parents and Communities’ Assets to Control Under-Five Child Malaria in Rural Benin, West Africa -- Health Assets and Public Policy -- Strengthening Asset Focused Policy Making in Hungary -- How Forms of Social Capital Can Be an Asset for Promoting Health Equity -- Internal and External Assets and Romanian Adolescents’ Health: An Evidence-Based Approach to Health Promoting Schools Policy -- Bringing It All Together: The Salutogenic Response to Some of the Most Pertinent Public Health Dilemmas.
Keywords: Public health; Health promotion; Health administration; Public Health; Health Promotion and Disease Prevention; Health Administration